Clinical and radiographical changes in patients with periodontitis treated with platelet-rich plasma - Maritza Peña Sisto; Lissette Santos Toledo (Centro Provincial de Información de Ciencias Médicas, 2017)
The case reports of two patients with chronic periodontitis of the adult are presented, to whom the initial phase of the treatment and the periodontal surgery with the mucous periostical Kirkland flap technique was carried out, which facilitated the access to bone defects, as well as radicular curettage and smoothing out, careful washing of the receptor bed with physiological salt solution and then perfusion of platelet-rich plasma. Significant changes were obtained in the improvement of gum clinical features during healing and signs of bone integration after three months of treatment. This procedure constitutes a permanent and effective way to correct periodontal bone destructions by means of the activation of the repair process.